Development of Fermentation Technique for High Cell Density Cultivation of Baker's Yeast (Saccharomyces Cerevisae) - Ahmad Ariff (2005)
The yeast, Saccharomyces cerevisae, isolated from fermented food was used in this study. Batch fermentation studies of S. cerevisae in a 2 L stirred tank fermenter were undertaken to generate kinetic growth data for the design of continuous and fed-batch fermentation. The variables studied in batch fermentation include the use of different concentrations of carbon and nitrogen sources and the effect of agitation speed (ranging from 200 to 1200 rpm), on the performance of each fermentation. The fermenter equipped with the multifermenter control system (MFCS) was used in exponential fedbatch fermentation to control the feeding rate of the glucose to the culture according to the proposed algorithm. In batch fermentation, final cell concentration obtained increased proportionally with initial glucose concentration up to 120 g/L, which gave a constant cell yield of 0.13 g celllg glucose. However, the specific growth rate (p) reduced with increase in glucose concentration. The amount of ethanol accumulated in the culture also increased proportionally with increasing glucose concentration. In term of overall productivity, the highest (0.35 g/L.h) was obtained in fermentation using 80-120 g/L glucose. Different growth characteristics of yeast were also observed at different agitation speeds.The final cell concentration increased from 29.76 g/L at agitation speed of 200 rpm to 41.90 g/L at 1000 rpm. However, a slight decrease in cell viability was observed with increasing agitation speed. The fermentation with controlled DOT throughout the fermentation (via agitation speed) did not improve the fermentation performance. For example, maximum cell concentration obtained in fermentation where DOT was controlled at 40% saturation was only 20.38 g/L. From this study, it can be suggested that the optimal medium composition and culture condition for batch cultivation of Baker's yeast are as follows; glucose (100 g/L); yeast extract (25.0 g/L); peptone (11.80 g/L); agitation speed (1000 rpm); air flow rate (1 vvm); DOT not controlled; and pH controlled at 5.5. In this fermentation run, the final cell concentration obtained was 41.90 g/L which gave the cell yield and overall productivity of 0.24 g/g and 2.41 g/L.h, respectively. Although higher overall productivity was obtained in continuous culture (5.53 g/L.h) operated at a dilution rate of 0.3 h-', the concentration of cell (18.43 g/L) in outflow was very much lower than in batch culture. In addition, the cell yield obtained in continuous culture 0.21 g/g was slightly lower than those obtained in batch fermentation. The models based on Monod and Luedeking-Piret equations were found suitable to describe the growth of S. cerevisiae, glucose consumption and ethanol production in batch and continuous fermentation processes. Kinetic parameters such as b,,, Ks and Yds were estimated and used to verify the experimental data. High cell density cultivation was achieved in exponential fed-batch fermentation with the feed rate of the substrate increased according to the exponential growth of the yeast at specific growth rate (0.1 to 0.4 h-') below the maximum. The highest cell concentration (89.97 glL) was obtained at specific growth rate of 0.1 h", which was associated with very small quantity of ethanol accumulated and residual sugar was not detected in the culture during the fermentation. The cell yield (0.72 g celllg glucose) and overall productivity (3.8 g1L.h) obtained in fed-batch fermentation was significantly higher than those obtained in batch fermentation. The sugar limitation that was maintained during exponential fed-batch fermentation was successfully utilized to enhanced biomass yield and substrate cultivation hence.